Active methodologies (virtual or physical resources) used in the teaching or learning process in the subject of Biology for the topic of cells at the "Luis Cordero" Educational Institution (Research, Society and Development, 2022)
This project is based on the identification of active methodologies (virtual or physical resources) that are used in the teaching or learning process in the subject of "cell", in the first year of BGU. This research was conducted at the "Luis Cordero" Educational Institution in the Azogues canton. In order to collect the necessary information, different methodological instruments were used, in this case, field diaries, surveys and pretest; the information obtained from both the teacher and the learner is related to the variety of active methodologies (virtual or physical resources) used in the classes. The data obtained were studied in the following way: the pretest identified the learning difficulties that the trainees have with respect to the basic concepts of Biology, and above all, the confusion of biological terms that exists was understood. The survey also obtained results on how the students perceive the classes taught in the subject of Biology, in this case, a combination of theoretical and lecture that leads to memorization. Then, in the apprentices it was evidenced the lack of motivation they have to attend and learn these biological concepts. In conclusion, it would be of great help to use active methodologies such as web pages that allow teaching (teacher) and learning (student) these Biology topics.